Argon plasma coagulation in the treatment of hemorrhagic radiation proctitis - Mehmet BÜYÜKBERBER; M. Cemil SAVAŞ; Murat Taner GÜLŞEN; Mehmet KORUK; Abdurrahman KADAYIFÇI (Turkish Journal of Gastroenterology, 2019)
-